The use of social media as a means of improving English skills - Ngadwan, Ngadwan; Adijaya, Nuryansyah (CV. Mitra Palupi, 2020)
Background: Each user has their smartphone to do communication. The user tends to use social media to communicate each other. Now in pandemic of COVID 19, the teachers do mostly communication to the students and/or to the expatriate teacher are using English.Purpose: This study is aim to reveal on teacher perspective on what extent that the social media help them to enrich the English skills.Design and methods: This study is conducted by using narrative inquiry method. The narrative inquiry method aims to reveal certain topic referring to stories and/or experiences. There are 9 participants who works as teacher at international schools at Tangerang. The participants’ selection is using purposive sampling strategy as knowing the participants will give their stories to only their close friend. The data is validated by triangulation of data source technique. The triangulation of data source technique is done by crosschecking the data among participants’ responses.Results: This study revealed that social websites and the content of media give more impact to the improvement of English skills of the teachers. This research recommends to investigate a certain categories social media on specific skills and/or to investigate a certain platform in promoting the English learning process.